Life forms variability of mediterranean sclerophyllous forests (Plant Ecology, 1990)
Variations in Raunkiaer's life-forms spectra for mature Quercus ilex forest stands in N-Mediterranean basin were examined in order to assess their predictability in local vegetation analysis. Physiognomic variations in Quercus ilex communities appear to be mainly determined by structural variations due to intrinsic characteristics (long-term human disturbance all over their range) and to different dynamical status of the stands, without any geographical pattern.